Improving grade 10 students’ performance using the contextualized learning resource material on the theory of evolution - Norcio, Joaquin; Depalco, Edelyn; Coles, Rhea (Journal of Social Sciences and Management Studies, 2024)
This quasi-experimental study investigated the effectiveness of contextualization in teaching the hardest curricular content in biology – evolution. It tested a Contextualized Learning Resource Material (CLRM), a modular learning material developed by Norcio (2023), among two comparably similar heterogenous Grade 10 classes. The findings of the study showed that (a) the performance of the students under the comparison group, wherein the LM and the SLM were utilized, improved from a mastery level of “Low” to “Moving Towards Mastery”. On the other hand, the performance of the students in the experimental group, wherein the CLRM was utilized, improved from a mastery level of “Low” to “Closely Approximating Mastery”; (b) there is a significant difference in the pre-test and post-test scores of the students both in the comparison group and experimental group, and (c) there is a significant difference between the post-test scores of Grades 10 students taught under the experimental group and the comparison group. Therefore, the CLRM should be used either with the LM and SLM or alone in the instruction for the topic evolution.